Inovasi Hardware untuk Memperkuat Sistem Informasi Manajemen pada Bank Syariah Indonesia - Ayu Hani Marsani; Dinda Nurayuni Humaira; Try Wahyuni Mawatdah; Nurbaiti Nurbaiti (Universitas 45 Surabaya, 2026)
This study aims to analyze the role of hardware innovation in strengthening the Management Information System (MIS) at Bank Syariah Indonesia (BSI) after the merger. The background of this study addresses the challenges of integrating hardware infrastructure from three former banks, which initially caused several system disruptions affecting digital service stability and customer trust. This research employed a qualitative descriptive method with a literature review approach, utilizing scientific articles, official reports, and other relevant sources related to digital transformation in Islamic banking. The results show that hardware innovations, such as increasing server capacity, optimizing data centers, strengthening cybersecurity networks, and upgrading operational devices, significantly contribute to improving MIS performance, particularly in transaction speed, operational efficiency, and data security. The study concludes that strengthening hardware infrastructure is a strategic factor in supporting the success of BSI’s digital transformation. Future research is recommended to involve primary data through interviews or direct observation within BSI to obtain a more in-depth and comprehensive analysis.